PENERAPAN GREEN TRADE STRATEGY DALAM MENDUKUNG KEPABEANAN HIJAU DI INDONESIA - Firmansyah, Amrie; Kurniawan, Indra (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
Global climate change and its impact on the movement of people and goods pose new challenges to Indonesia's national security and economy. Based on data from 91 observation stations from the Meteorology, Climatology, and Geophysics Agency (BMKG), the normal air temperature for the period 1991–2020 in Indonesia is 26.8 °C, with an average air temperature in 2022 of 27.0 °C. In Indonesia and the world as a whole, 2016 was the hottest year with a temperature anomaly of 27.4 °C. Indonesia is recorded as contributing 259.1 million metric tons of CO2 in 2021 and is projected to increase by 29.13% to 334.6 million metric tons of CO2 in 2030. As a response to climate change, the idea of green customs has emerged. The aim is to increase customs capacity, monitor and facilitate legal trade, and prevent illegal trade in environmentally sensitive commodities with Multilateral Environmental Agreements. Various countries in the world are required to realize Green Customs. This study aims to determine the implementation of Green Customs in various countries and recommend policies to support the implementation of Green Customs in Indonesia. The method used in this research is a systematic literature review. The results of the study show that the World Customs Organization focuses on implementing green customs through cooperation between parties; United States Customs releases a green trade strategy; countries in Africa make use of AcFTA; and ASEAN member countries need to harmonize non-tariff measures. Policies that can be considered include providing green trade incentives, strengthening environmental law enforcement, accelerating green innovation, increasing climate resilience and resource efficiency, maximizing the use of free trade agreements for green products, maximizing export financing institutions for green industries, and harmonizing non-tariff measures